PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATAN HASIL BELAJAR MATEMATIKA - Elita Mega Silvia Wijaya; Rudy Setiawan; Inarti Kresna Milla (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
The aim of this research is to produce Student Worksheets based on Problem Based Learning to improve student learning outcomes in junior high schools. This research uses the 4 D device (FOUR D MODEL). The development procedure includes analysis, design, development and implementation stages. The test subjects in this research were 16 class VII junior high school students consisting of 8 girls and 8 boys. Data collection was carried out using validation and test techniques. Based on the results of data analysis, student worksheets based on Problem Based Learning can be applied and carried out validly. Based on the results of the development research that has been carried out, it can be concluded that the Problem Based Learning model learning tools meet the very valid category with an average value for the lesson plan validator of 3.6 in the very valid category, student worksheets of 3.5 in the very valid category, response teachers towards student worksheets 3.2 in the very valid category, student responses to student worksheets 3.7 in the very valid category, the results of student worksheets is 3.1 in the very valid category, and the group test results is 3.5 in the very valid category.